2018
DOI: 10.29259/jmbs.v16i1.6247
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Work-Life Balance Terhadap Komitmen Organisasi, Kepuasan Kerja, Dan Motivasi Kerja Terhadap Kinerja Individu Pada Karyawan Perusahaan Asuransi Di Jakarta

Abstract: ABSTRAK                                                                                                                                   Tujuan penelitian – Penelitian ini bertujuan untuk meneliti pengaruh work-life balance terhadap komitmen organisasi, kepuasan kerja, dan motivasi kerja. Selain itu, juga meneliti pengaruh komitmen organisasi, kepuasan kerja, dan motivasi kerja terhadap kinerja individu. Desain/Metodologi/Pendekatan – Penelitian dilakukan pada 190 karyawan di perusahaan asuransi di Jakarta. J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 1 publication
0
15
0
23
Order By: Relevance
“…According to research by Kusuma and Lina (2018), it was explained that their successfully confirmed the positive impact of employee satisfaction on employee performance, The results of this study adding the facts of employees who obtain a job satisfaction will provide a good and positive employee performance. According to the research by Rene and Wahyuni (2018) it explains that the job satisfaction supports a significant impact on individual performance. However, the different result obtained from Saufa and Maryati (2017) which stated that there has no effect of job satisfaction that can increased the Therefore, during their work, nurses has to own a good loyalty and have a serious manner of work by saving other people life.…”
Section: Introductionmentioning
confidence: 99%
“…According to research by Kusuma and Lina (2018), it was explained that their successfully confirmed the positive impact of employee satisfaction on employee performance, The results of this study adding the facts of employees who obtain a job satisfaction will provide a good and positive employee performance. According to the research by Rene and Wahyuni (2018) it explains that the job satisfaction supports a significant impact on individual performance. However, the different result obtained from Saufa and Maryati (2017) which stated that there has no effect of job satisfaction that can increased the Therefore, during their work, nurses has to own a good loyalty and have a serious manner of work by saving other people life.…”
Section: Introductionmentioning
confidence: 99%
“…Work-life balance is the extent to which individuals can balance between roles in work and outside of work [11]. According to the research conducted by Redwood (2014) in JobStreet.com in the United Kingdom concludes that the organizations that encourage employees to have a balance between work and personal life will earn 20% more income than organizations that do not [12]. This is also supported by other research that employees who can achieve a balance between work and family will have positive and loyal behaviors in organizations [13].…”
Section: Introductionmentioning
confidence: 99%
“…Research according to Berk and Gundogmus (2018) states that WLB has a significant influence on employee commitment, so it can be said that when employees are able to work without ignoring all aspects of work life, personal, family, spiritual, and social, it will encourage these employees to have a commitment. On the other hand, research conducted by Rene (2018) found that WLB did not have a significant effect on employee commitment. So it needs to be reviewed again related to the research gap between WLB and employee commitment.…”
Section: Introductionmentioning
confidence: 85%